Pengaruh Beban Kerja Terhadap Stres Kerja dan Kinerja Karyawan PT. Putra Mahalona - -, Mutiara Suci Ramadhani; Anwar Ramli; Abdi Akbar (STIE-PMCI, 2022)
This study aims to determine the effect of workload on work stress and employee performance at PT. Putra Mahalona. Data collection was carried out using a questionnaire with a sample of 68 respondents with a sampling technique that is purposive sampling technique. Questionnaire data processing uses the SEM-PLS model which is processed with SmartPLS 4.0 software.The results of this study indicate that workload has an effect on work stress with a t-statistic value greater than 1.66, namely 4.764, workload has an effect on employee performance with a t-statistic value greater than 1.66, namely 1.810, work stress has an effect on performance employees with a t-statistic value greater than 1.66, namely 8.545. Through improving the currently low indicators, companies should be able to better manage employee work stress. This can be achieved by avoiding factors such as heavy workloads which can cause work-related stress which can also impact employee performance.